Myeloid sarcoma: clinical features, bone marrow hematological characteristics, and prognosis of 20 cases - LIU Xian, HUANG Lifang, MENG Fankai, MENG Li, WANG Zhiqiong (Zhenduanxue lilun yu shijian, 2025)
Objective To investigate the clinical features and prognosis of myeloid sarcoma (MS). Methods A retrospective analysis was conducted on the clinical data and bone marrow hematological test results of 20 MS patients diagnosed and treated in our department from December 2016 to January 2022. Clinical data were summarized, and the prognosis of three types of MS patients (isolated MS, MS with intramedullary lesions, and secondary MS after AML treatment) was analyzed. Results Among the 20 MS patients, 10 were male and 10 were female. The median age was 37 years (range: 6-62). The most common site of MS was the nasopharynx (25%), followed by the mediastinum (10%), thoracic vertebrae (10%), lymph nodes (10%), breast (10%), cervix (5%), eyes (5%), spleen (5%), testes (5%), abdomen (5%), sacrococcygeal region (5%), and pylorus (5%). There were 10 cases of isolated MS, 6 cases of MS with intramedullary lesions, and 4 cases of secondary MS after AML treatment. Immunohistochemical positive rates, from high to low, were CD99 (100%), CD43 (95%), MPO (95%), BCL-2 (90%), CD68 (75%), CD117 (50%), and CD34 (45%). TdT, CD3, CD20, and PAX-5 were all negative. Fusion gene testing was performed on 17 patients, with 7 positive results (7/17), including 3 cases of AML1-ETO (3/17), 2 cases of CBFβ-MYH11 (2/17), 1 case of MLL-AF10 (1/17), and 1 case of BCR/ABL1 (1/17). Chromosomal karyotype analysis was performed on 17 patients, and 6 showed abnormal karyotypes (6/17). Fluorescence in situ hybridization (FISH) was performed on 4 patients, with 3 positive results (3/4). Genetic mutation testing was conducted on 10 patients, with 9 positive results (9/10). The most frequent mutation was CEBPA (5 cases), followed by NRAS, FLT3, NPM1, and KIT (2 cases each). During the follow-up period of 1-38 months, 7 of the 20 MS patients died, and 13 survived. The cumulative survival rates at 1, 2, and 3 years were 75%, 70%, and 65%, respectively. No statistically significant difference in survival was observed among isolated MS, MS with intramedullary lesions, and secondary MS after AML treatment (P=0.718). Conclusion MS can occur in a wide range of anatomical sites. Pathological immunohistochemical markers, including CD43, CD99, CD68, MPO, CD34, and CD117, are critical for its diagnosis. Bone marrow hematological examination results can provide a basis for targeted therapy. There is no survival difference among the three types of MS patients, and systemic treatment is recommended for all patients.